Preclinical exploration and current clinical applications of immunotherapeutic strategies for hepatocellular carcinoma - Yu, Haoyang; Wen, Xin; Cui, Mengying; Liu, Shui (Frontiers in Immunology, 2026)
Hepatocellular carcinoma (HCC) is the sixth most common cancer and the third leading cause of cancer death worldwide. Treatment of HCC has shifted from traditional modalities to immunotherapy-centered combination strategies. While the current immunotherapies can substantially reduce the risk of death for patients with HCC, overall survival improvement is limited because of tumor heterogeneity and an immunosuppressive microenvironment. Moreover, the widespread application of these treatments is challenged by high costs, drug resistance, and frequent adverse events. This review outlines the mechanisms of the available HCC immunotherapeutics and summarizes the preclinical explorations of these treatments. We also describe the current clinical applications and underlying mechanisms and discuss issues of resistance and heterogeneity. We further provide an overview of emerging approaches against cancer platforms in HCC, aiming to provide practical references for clinical immunotherapy of HCC.